Shoulder tensiomyography and isometric strength in swimmers before and after a fatiguing protocol - Stella, A. B.; Cargnel, A.; Raffini, A.; Mazzari, L.; Martini, M.; Ajcevic, M.; Accardo, A.; Deodato, M.; Murena, L. (Journal of Athletic Training, 2024)
Context: Shoulder muscles are active during front-crawl swimming to provide propulsion and stabilize the glenohumeral and scapulothoracic joints. Researchers have proposed that fatigue might contribute to altered activation of these muscles and represent a risk factor for injuries. Tensiomyography (TMG) might function as a noninvasive tool to detect changes in contractile measures of the skeletal muscles due to exercise-induced neuromuscular fatigue, though it has not yet been used in the shoulder muscles of swimmers. Objective: To assess the effects of a fatiguing swimming protocol on shoulder muscle TMG measures and isometric strength in competitive swimmers. Design: Cross-sectional study. Setting: Swimming pool facility. Patients or Other Participants: A total of 14 young front-crawl competitive swimmers (11 males and 3 females; age = 21 ± 3 years [range, 17-26 years], height = 1.78 ± 0.06 m, mass = 73.1 ± 9.2 kg). Main Outcome Measure(s): Participants completed TMG and isometric strength assessments before and after 30-minute, high-intensity swim training. The TMG assessment was performed on 7 muscles of the shoulder according to front-crawl biomechanics and the applicability of the technique to obtain data, such as time to contraction and muscle-belly radial displacement. Isometric strength was assessed using a digital handheld dynamometer during shoulder flexion, extension, external rotation, and internal rotation. Results: Fatigue induced a smaller radial displacement, mostly observable in latissimus dorsi (-1.0 mm; 95% CI = -1.7, -0.3 mm; P = .007) and pectoralis major muscles (-1.4 mm; 95% CI = -2.4, -0.4 mm; P = .007). Only shoulder extension showed an isometric strength reduction after the fatiguing protocol (-0.03 N/kg; 95% CI = -0.05, -0.01 N/kg; F1,13 = 4.936; P = .045; ?p2 = 0.275). Conclusions: This study provides preliminary evidence for the usefulness of TMG to detect fatigue-induced changes in contractile properties of the shoulder muscles in swimmers, in particular the latissimus dorsi and pectoralis major.